A Study on Intercultural Communicative Competence of Chinese English Majors Based on Teacher Report Data - Zhou Jingjing; Florence Gilliam Kayad; Vimala Govindaraju (Research and Advances in Education, 2024)
Most previous studies have used student self-reported data to investigate their proficiency in intercultural communication competence (ICC), while few have examined it from their teacher’s perspective. This paper reports a qualitative case study on English major students’ ICC in Chinese higher education. The instrument was adapted from the scale of Intercultural Ability developed by Fantini (2007). The data were collected from in-depth interviews from 8 English major teachers and analyzed by thematic analysis. The findings indicated that students had general intercultural knowledge, open attitudes and limited intercultural skills.